2020
DOI: 10.1021/acs.molpharmaceut.9b01281
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Preclinical Evaluation of a 124/131I-Labeled Radiotracer for the Detection of Mesothelin-Overexpressing Cancer

Abstract: Mesothelin is a molecular biomarker of many types of solid cancers, which may represent a highly promising new target in the development of cancertargeted diagnostic agents. A human anti-mesothelin antibody with a low molecular weight, ET210sc, was applied; this antibody has potent affinity and can penetrate tissue quickly and stably without causing immunoreactions. We developed a new 124/131 I-labeled radiotracer of ET210sc. The 124/131 I-labeled ET210sc radiotracer showed excellent radiochemical quality (wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…31 Wang used 124/131 I to label and image the MSLN antibody fragment (scFv-Fc) ET210sc and detected high uptake of the probe in MSLN-overexpressing tumors. 32 By comparing 124 I-anti-MSLN with 124 I-ET210sc, we found that the PET/CT images of 124 I-anti-MSLN (7.4 MBq) were better than those of 124 I-ET210sc (11.1 MBq). The T/M value of 124 I-anti-MSLN (10.56 ± 1.12) was higher than that of 124 I-ET210sc (6.11 ± 2.18) 3 days postinjection.…”
Section: ■ Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…31 Wang used 124/131 I to label and image the MSLN antibody fragment (scFv-Fc) ET210sc and detected high uptake of the probe in MSLN-overexpressing tumors. 32 By comparing 124 I-anti-MSLN with 124 I-ET210sc, we found that the PET/CT images of 124 I-anti-MSLN (7.4 MBq) were better than those of 124 I-ET210sc (11.1 MBq). The T/M value of 124 I-anti-MSLN (10.56 ± 1.12) was higher than that of 124 I-ET210sc (6.11 ± 2.18) 3 days postinjection.…”
Section: ■ Discussionmentioning
confidence: 83%
“…Weele used TFP-N-sucDf to conjugate AMA to label 89 Zr, and the results showed that it is possible to noninvasively observe human pancreatic tumors subcutaneously implanted in mice with 89 Zr-AMA . Wang used 124/131 I to label and image the MSLN antibody fragment (scFv-Fc) ET210sc and detected high uptake of the probe in MSLN-overexpressing tumors . By comparing 124 I-anti-MSLN with 124 I-ET210sc, we found that the PET/CT images of 124 I-anti-MSLN (7.4 MBq) were better than those of 124 I-ET210sc (11.1 MBq).…”
Section: Discussionmentioning
confidence: 99%